Synthetic fluid inclusions XX. Critical PTx properties of H2O–FeCl2 fluids. (1st January 2015) - Steele-MacInnis, Matthew; Lecumberri-Sanchez, Pilar; Bodnar, Robert J.
Abstract: Iron chloride is a common and abundant component in hydrothermal fluids in many geologic environments, yet the thermodynamic and PTx properties of FeCl2 -bearing aqueous fluids are poorly known. In this study we have used the synthetic fluid inclusion technique to characterize the PTx conditions along the critical curve of the system H2 O–FeCl2 . For a given temperature or salinity, the critical pressure in the H2 O–FeCl2 system is lower than that in the H2 O–NaCl system. In contrast, the critical curves of aqueous solutions of other divalent-cation chlorides, such as MgCl2 and CaCl2, are at higher pressure than that of NaCl solutions of equivalent temperature or salinity. The results of this study provide the first quantitative constraints on the PTx extent of liquid–vapor immiscibility for FeCl2 -rich fluids. Owing to the low pressure along the critical curve compared to other common aqueous chloride systems, immiscibility of FeCl2 -rich fluids appears to be limited to relatively low pressures, or relatively shallow levels in the crust, compared to other saline hydrothermal fluids.